The association of seasonal changes with conception and birth in a group of Iraqi women - Harmoosh, Shaima K. (Journal of the Faculty of Medicine Baghdad, 2018)
Background: Temperatures and seasons have been suggested as environmental factors that influence fecundity in mammals. It has been reported that there is a link between human fertility and seasonal changes.Objectives: The aim of the study was to assess whether the seassonal changes in tempreture, humidity, light intensity and light duration do influence fecundity and reproduction in the study group of Iraqi women who were from Baghdad.Patients and Methods:This study was conducted on 1638 randomly selected womenn who were from Baghdad city and were normaly delivered at Al- Elwiyah Maternity Teaching Hospital during 2014. A detailed questionnaire form was filled through direct interview with the mothers shortly after delivery. The climate information were taken from the Iraqi Meteriological Department and Research Center of Solar Energy, Ministry of Science and Technology.Results: Results obtained confirmed that there was a highly significant seasonal variations in birth and conception rates at different months of the year, The conception rates were significantly negatively correlated with mean temperature rates, light intensity and light duration and significantly but positively correlated with mean percent humidity.Conclusion: These results confirm that there was a significant seasonal nfluence on human reproduction among the study group.